Preferential growth of Au on CdSe quantum dots using langmuir-blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2014)
Oleyl amine capped CdSe quantum dots (QD) were synthesised by hot injection technique. These QDs formed a self-assembled monolayer on an aqueous subphase of a Langmuir-Blodgett (LB) trough. Here, in this report we introduced a simple but very efficient route to form a metal (Au)-QD hybrid nanostructure via the LB technique. In this method, the metal counterpart of the hybrid nanostructure could be deposited exclusively on one side of the QDs. The formation of stable monolayer of QDs was evidenced from a surface pressure-area (P-A) isotherm. The development of gold tip was confirmed and monitored by detailed TEM study on the monolayer deposited on TEM grids from the LB trough. Other characterizations like UV-Vis spectroscopy, FTIR, XPS and EDX also suggested the same. Oleyl amine was shown to act both as a reducing agent as well as a capping agent in this strategy.

Seeding of Au on CdSe/CdS nanoplates using Langmuir-Blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2016)
Oleyl amine capped CdSe/CdS nanoplates were synthesized by hot injection technique which formed a stable monolayer over both a water subphase and an aqueous HAuCl4 subphase using a Langmuir-Blodgett trough. Au islands were generated at the edge as well as on one specific surface of the flat nanoplates by exploiting the reducing capacity of oleyl amine to form Au nanoseeds from AuCl4- ions. The initial Au nanoseeds changed to a shell surrounding these nanoplates on prolonged exposure to the subphase containing the Au precursor. Monolayer of the hybrid structures was deposited onto suitable substrates for characterization by a number of different techniques and to study the photocatalytic activity. The same substrate with the monolayers could be re-used in several cycles of photocatalysis.